2018
DOI: 10.1177/0300060518780138
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body weight perception and weight-related behaviours

Abstract: ObjectivesThis study aimed to examine the prevalence of weight misperception and to explore the association of weight perception with physical activity and dietary intake.MethodsA population-based, nationally representative cross-sectional survey was conducted of 920 Thai adolescents aged 13 to 24 years. Respondents were selected using stratified multistage sampling. Respondents who agreed to participate were asked to complete the Youth Risk Behavior Questionnaire.ResultsFemales were more likely than males to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
4
16
1
Order By: Relevance
“…Interestingly, among the persons that overestimated their weight, female individuals were more frequently eutrophic, whereas males were more frequently underweight. These results are in line with a North American study of more than 6500 teenagers [ 35 ], and another investigation of 1,643 teenagers from Italy and more recently in Thailand [ 33 , 36 ]. Thus, there is strong evidence to support that there are important differences in self-perceived weight between the sexes and that female individuals tend to overestimate their weight.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, among the persons that overestimated their weight, female individuals were more frequently eutrophic, whereas males were more frequently underweight. These results are in line with a North American study of more than 6500 teenagers [ 35 ], and another investigation of 1,643 teenagers from Italy and more recently in Thailand [ 33 , 36 ]. Thus, there is strong evidence to support that there are important differences in self-perceived weight between the sexes and that female individuals tend to overestimate their weight.…”
Section: Discussionsupporting
confidence: 91%
“…Weight misperception is the over-or underestimation of one's weight. Unlike most previous studies (46)(47)(48)(49)(50)(51) that compared body weight perception and obesity and categorised them as over-, under-or correct estimation, to measure body weight misperception, the current study subdivided weight misperception levels into five categories by matching them to actual weight levels, because, for example, in the case of overestimation, there is a difference between people of a healthy weight who perceive themselves as overweight and underweight people who perceive themselves as being of a healthy weight.…”
mentioning
confidence: 72%
“…In unison to our findings, earlier studies [ 17 , 28 ] conducted in this region revealed similar rates of weight misperception among participants with excess body weight. Nonetheless, despite of the existing controversy regarding how the perception of being overweight relates to weight related lifestyle behaviors; right perception on one’s body image is likely to have a positive influence on health behaviors [ 29 31 ]. Conversely, cultural and social influences particularly in SSA have been shown to impact body image perception [ 32 ].…”
Section: Discussionmentioning
confidence: 99%